Unit seven - Water use in agriculture: large-scale irrigation. [Training/Course material] - David, S.; Fraiture, Charlotte de; Atapattu, Sithara S.; Smith, L. (2009)
This unit provides an introduction to large-scale and formal irrigation systems. The first section introduces large-scale irrigation systems and looks at their role in poverty alleviation. The section analyses the positive and negative implications in the context of social, economic and environmental needs. Section 2 describes the types of irrigation systems based on governance and water sources and key implications of various irrigation system types. The following section deals with irrigation management by providing guidance on the management steps, design and assessment tools. It also looks at different options for irrigation financing such as water pricing. Section 4 explores investments in irrigation - types of investments, drivers for investments, priorities and social and environmental considerations. Unit aims: To introduce the linkages between investments in large-scale irrigation and poverty and to discuss possible positive and negative outcomes; To introduce standard irrigation system typologies based on governance and to understand the different types of water resources utilised; To introduce the steps and considerations involved in irrigation management, introduce basic assessment tools and discuss the main issues behind irrigation financing and water pricing; To provide an understanding of the different types of investment, when and where they are applied and how they are prioritised.